MEMORIES AND SPACES: LITERATURE FOR CHILDREN MEDIATING DIFFERENT TIMES - Souza, Renata Junqueira de [UNESP]; Quadros, Marta Campos de [UNESP] (Fundacao Univ Tocantins, 2020)
Literary narratives for children can build a rich net of meaning produced in different moments and spaces that compose human experience. Memory has been taken as a space for sharing this experience and narratives are its way of expressing itself. Literary narratives are part of this sharing and interpretation of the human being and, therefore, an element for reflecting on children's education. In this paper, we present the results of projects that include the presence the children's literature book Wilfrid Gordon Mac Donald Partridge (Fox 2012) in the classroom, where we develop reading activities, both in Brazil and Portugal. We take Harvey and Goudvis's (2007) and Girotto and Souza's (2010) ideas as a reference about metacognitive reading strategies. Our goal is to show how - when working with full literary texts - memory mediates diverse times and spaces, articulating literary narrative to the reader's repertoire as part of the comprehension process.
Keywords: Education; Children's Literature; Memory; Reading Strategies; Teaching Literature